Sound and Sense / An Introduction to Poetry - Perrine Laurence (Harcourt Brace Jovanovich, Publishers, 1977)
Preface, The Elements of Poetry, What is Poetry, Reading the Poem, Denotiation and Connotation, Imagery, Figurative Language 1: Metaphor and Personification and Metonymy, Figurative Language 2: Symbol and Allegory, Allusion, Meaning and Idea, Tone, Musical Devices, Rhythm and Meter, Sound and Meaning, Pattern, Bad Poetry and Good, Good Poetry and Great, Poems for Further Reading.
Preface, The Elements of Poetry, What is Poetry, Reading the Poem, Denotiation and Connotation, Imagery, Figurative Language 1: Metaphor and Personification and Metonymy, Figurative Language 2: Symbol and Allegory, Allusion, Meaning and Idea, Tone, Musical Devices, Rhythm and Meter, Sound and Meaning, Pattern, Bad Poetry and Good, Good Poetry and Great, Poems for Further Reading.